Dissection of the Left Coronary Artery after Surgical Aortic Valve Replacement - Sadraddin, Haval; Krüger, Ulrich; Börgermann, Jochen; Gerçek, Mustafa (The Thoracic and Cardiovascular Surgeon Reports, 2021)
Our report presents a 73-year-old female patient with severe aortic stenosis who was admitted to our department for a surgical aortic valve replacement. After an uneventful surgery, a worsening low cardiac output syndrome with signs of myocardial ischemia occurred. Immediate angiography revealed a diffuse left coronary dissection starting from the ostium extending to the periphery of the left coronary system. The diffuse nature of the dissection ruled interventional management out and thus has been treated with urgent coronary bypass surgery. However, after an antecedent favorable course, the patient died 2 months later due to pneumonia resulting in septic shock.
Keywords: ischemia/reperfusion; myocardial protection/cardioplegia; surgery; complication